2022
DOI: 10.4103/atm.atm_487_21
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of bronchoscopy in sputum-negative pulmonary tuberculosis patients and its correlation with clinicoradiological features

Abstract: CONTEXT: Tuberculosis (TB) remains endemic in Saudi Arabia. Little local data have been reported on bronchoscopic evaluation of sputum-negative pulmonary TB patients, which poses a significant diagnostic and therapeutic challenge. AIMS: To determine the diagnostic value of bronchoscopy and bronchoalveolar lavage (BAL) and its correlation with clinical and radiological features in sputum-negative, culture-confirmed pulmonary TB patients. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Generally, TBLB culture is not considered useful for diagnosing mycobacteria, including TB and mycobacterium avium complex 2 , 3 . In sputum-negative TB patients, there is no difference in the diagnostic rate between combined BAL and TBLB histology and combined BAL, TBLB histology, and TBLB culture 8 . All MAC patients who exhibited positive TBLB findings also showed positive acid fast bacilli in smear or/and culture 9 .…”
Section: Discussionmentioning
confidence: 90%
“…Generally, TBLB culture is not considered useful for diagnosing mycobacteria, including TB and mycobacterium avium complex 2 , 3 . In sputum-negative TB patients, there is no difference in the diagnostic rate between combined BAL and TBLB histology and combined BAL, TBLB histology, and TBLB culture 8 . All MAC patients who exhibited positive TBLB findings also showed positive acid fast bacilli in smear or/and culture 9 .…”
Section: Discussionmentioning
confidence: 90%
“…In some cases, this may reflect the simple fact that even culture is not perfectly sensitive and may in part relate to ambiguities of obtaining consistent sputum samples. On the other hand, more comprehensive samples like bronchoalveolar lavage (BAL) have been shown to detect over 80% of clinically diagnosed smears and GeneXpert-negative TB [ 31 ]. This reveals that part of the problem may be in obtaining an appropriate bacillus-containing specimen by routine sputum sampling method.…”
Section: Discussionmentioning
confidence: 99%
“…Our aim was to assess the value of BAL in a real-world scenario. The few studies addressing this issue mainly include patients with a known final diagnosis of PTB and look at the diagnostic yield of bronchoscopy among them [18,26,27]. This method of selection can induce selection bias, underlined by the studies' high diagnostic yield of bronchoscopy (57-83%), and does not reflect real-life decision-making for patients hospitalized with HS-PTB.…”
Section: Discussionmentioning
confidence: 99%
“…However, the added diagnostic value of BAL in HS-PTB cases remains unknown. A limited number of studies reported the yield of BAL in this patient population, and their results showed high variability of diagnostic performances [16][17][18][19]. Among these studies, only a few included consecutive patients, were conducted in the in-patient setting, or used cohorts of patients with other final diagnoses to understand its added diagnostic value.…”
Section: Introductionmentioning
confidence: 99%